Efficacy of combination scalp acupuncture for post-stroke cognitive impairment: a systematic review and meta-analysis - Li, Song; Dai, Anhong; Zhou, Yihao; Chen, Xu; Chen, Yizhou; Zhou, Li; Yang, Xiaolin; Yue, Mengqi; Shi, Jing; Qiu, Yong (Frontiers in Neuroscience, 2024)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the efficacy of combination scalp acupuncture in treating post-stroke cognitive impairment.MethodsA comprehensive search was conducted across eight databases: PubMed, Web of Science, Cochrane Database, Embase, CBM, CNKI, WanFang, and VIP, targeting randomized controlled trials (RCTs) published from the inception of these databases until October 24, 2024. The inclusion criteria focused on RCTs that compared scalp acupuncture with conventional treatments as therapeutic interventions for patients suffering from post-stroke cognitive impairment (PSCI). The effectiveness of these treatments was evaluated using various outcome measures, including the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA), as well as P300 latency and amplitude, which collectively assess cognitive function. Two independent reviewers conducted a risk of bias (ROB2) assessment, and data analysis was performed using Review Manager (RevMan) version 5.4.ResultsThis analysis included a total of 28 studies involving 1,995 patients. However, according to the standards of the ROB2 tool, most of these studies exhibited various methodological issues. The comprehensive analysis indicates that the efficacy of combined scalp acupuncture in treating post-stroke cognitive impairment (PSCI) is superior to that of single treatments, as evidenced by improvements across multiple scales, including the Montreal Cognitive Assessment (MoCA), Mini-Mental State Examination (MMSE), Loewenstein Occupational Therapy Cognitive Assessment (LOTCA), P300 latency, and amplitude. Specifically, the overall effective rate was reported as (RR = 1.28, 95% CI: 1.14–1.45, p < 0.0001; I2 = 51%, random effects model). The mean differences for the various scales were as follows: MoCA (MD = 3.55, 95% CI: 2.68–4.41, I2 = 93%, random effects model), MMSE (MD = 3.78, 95% CI: 2.83–4.73, I2 = 94%, random effects model), LOTCA (MD = 9.70, 95% CI: 7.72–11.69, I2 = 57%, random effects model), P300 latency (MD = −21.83, 95% CI: −26.31 to −17.35, I2 = 55%, random effects model), and amplitude (MD = 1.05, 95% CI: 0.76–1.34, I2 = 0%, fixed effects model), demonstrating low, medium, and high levels of heterogeneity, respectively. Notably, one study reported an adverse event related to participant withdrawal during the study.ConclusionCombination scalp acupuncture exhibits superior efficacy compared to single-treatment modalities in patients with post-stroke cognitive impairment (PSCI). However, the higher risk of bias (ROB) in the included trials suggests that the quality of evidence about these assessment results may be compromised. Therefore, there is an urgent need for additional high-quality clinical trials to further validate the efficacy and effectiveness of combined scalp acupuncture in treating PSCI, ultimately enhancing the overall level of evidence.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024519200.